Peningkatan Pemahaman Pasangan Usia Subur Melalui Penyuluhan Keluarga Berencana: Peningkatan Pemahaman Pasangan Usia Subur Melalui Penyuluhan Keluarga Berencana - Andi Masnilawati; Nia Karuniawati; Sitti Hadriyanti Hamang (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2022)
The use of contraceptives, if not supported by good and consistent family planning knowledge, will have a negative impact on unwanted pregnancies which can eventually lead to abortion. Therefore, it is necessary to have a strong and consistent understanding of contraceptive methods in the selection and use of contraception. Long-term contraceptive methods have proven to be the most effective in reducing pregnancy rates. However, until now long-term contraceptive methods are still not an option for most couples of childbearing age in Indonesia. According to data from Taeng Village, Gantarang Village, where family planning was developed in 2021, the number of registered couples of childbearing age was 378 active family planning with details of 7.93% injections, 2.38% pills, 1.32% IUD/IUD and implants. . 2.11%. Data shows that the use of long-term contraceptive methods is lower than short-term contraceptive methods, while long-term contraceptive methods are more effective than short-term contraceptive methods. The purpose of this community service is to increase the knowledge and understanding of couples of childbearing age about birth control through socialization and increasing types of contraceptives and their long-term use in Taeng Village, Kec. Pallangga, kab. Gowa. The method used in this service is the delivery of material about types of contraception and long-term contraceptive methods in the form of lectures, discussions and answers using powerpoints and leaflets for married couples as many as 14 people. The resulting coverage is an increase in community knowledge in Taeng Village with good knowledge (86%), sufficient (14%) and no more lack of knowledge about contraception. With the implementation of education through socialization and family planning counseling to enrich human life in Taeng Village, District. Pallangga, Gowa Regency, can increase the use of contraceptives in the community by introducing the mother's age, the number of children desired, and the mother's main health condition during the COVID-19 pandemic.